- Analisis Pasal 338 Jo Pasal 53 Ayat (1) KUHP dalam Putusan 596/PiD.B/2022/PN.Btm Tentang Penganiayaan: - - Erza Nabira; Sutrisno (Faculty of Law, Universitas Trisakti, 2024)
The punishment for the criminal offense of the application of Article 338 jo. Article 53 paragraph (1) of the Criminal Code committed by the defendant Putra Susanto bin Satiman, is based on the sanctions imposed by the judge on the defendant who committed the crime of attempted murder. The formulation of the problem in this article is whether the application of Article 338 jo. Article 53 paragraph (1) of the Criminal Code against the perpetrator of the crime of persecution in Decision Number 596/Pid.B/2022/PN Btm is appropriate or not? And whether the imposition of imprisonment for 7 (seven) years in Decision Number 596/Pid.B/2022/PN Btm is appropriate with the purpose of punishment. This research method uses a normative juridical research type that is descriptive analytical, using secondary data obtained through literature studies and processed qualitatively and then drawing conclusions in a deductive manner. The results that The application of Article 338 jo. Article 53 paragraph (1) of the Criminal Code was not appropriate because the defendant's actions did not constitute the crime of attempted murder, but rather persecution. In conclusion, the application of Article 338 jo. 53 paragraph (1) of the Criminal Code in Decision Number 596/Pid.B/2022/PN Btm is not appropriate.